2020
DOI: 10.3892/or.2020.7586
|View full text |Cite
|
Sign up to set email alerts
|

Spred2 inhibits epithelial‑mesenchymal transition of colorectal cancer cells by impairing ERK signaling

Abstract: Downregulation of the sprouty-related EVH1 domain protein 2 (Spred2) is closely associated with highly metastatic phenotypes in various tumors. However, the roles of Spred2 in the development and progression of colorectal cancer (CRC) are still largely unexplored. As anticipated, Spred2 expression was significantly downregulated in clinical tumor tissues. To restore Spred2 levels, Ad.Spred2, an adenoviral vector expressing Spred2, was transduced into CRC cells. It was revealed that Ad.Spred2 inhibited the prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…SPRED2 protein levels are strongly inversely associated with tumor progression and metastasis. In colorectal cancer and hepatocellular carcinoma, SPRED2 can inhibit the epithelial-to-mesenchymal transition and cell motility [ 67 , 68 ]. In our study, we found that SPRED2 can act as a tumor suppressor in BC as well, and that decreased levels of SPRED2 can increase their cell proliferation and migration capacity.…”
Section: Discussionmentioning
confidence: 99%
“…SPRED2 protein levels are strongly inversely associated with tumor progression and metastasis. In colorectal cancer and hepatocellular carcinoma, SPRED2 can inhibit the epithelial-to-mesenchymal transition and cell motility [ 67 , 68 ]. In our study, we found that SPRED2 can act as a tumor suppressor in BC as well, and that decreased levels of SPRED2 can increase their cell proliferation and migration capacity.…”
Section: Discussionmentioning
confidence: 99%
“…SPRED2 can inhibit activation of the Ras/Raf/ERK signaling pathway and the process of EMT. 32 , 33 Further, inhibiting the activation of the Ras/Raf/ERK signaling pathway can also reduce the secretion of matrix metalloproteinases and inhibit the migration and invasion of tumor cells. 70 Autophagy is closely implicated in the occurrence and treatment of tumor cells.…”
Section: Associations Between Spred Proteins and Diseasementioning
confidence: 99%
“…In prostate cancer, low expression of SPRED2 leads to increased levels of phosphorylated ERK, which promotes the proliferation and migration induced by various growth factors, thereby leading to carcinogenesis. 30 , 31 In addition to BC and prostate cancer, SPRED proteins have also been associated with colon cancer, 32 , 33 renal clear cell carcinoma, 34 lung tumors, 35 and esophageal cancer. 36 , 37 These findings indicate that SPRED proteins are important tumor suppressors that inhibit carcinogenesis and metastasis by inhibiting the Ras/Raf/ERK pathway.…”
Section: Associations Between Spred Proteins and Diseasementioning
confidence: 99%
“…Additionally, SPRED2 takes part in EndMT. For example, SPRED2 inhibits epithelial–mesenchymal transition (EMT) of colorectal cancer cells by inhibiting ERK signaling pathway, which contributes to alleviate colorectal cancer progression [ 17 ]. SPRED2 also inhibits the cell motility and EMT of keratinocytes induced by TGF-β1 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%